Taxonomy of three species of the genus Spinoncaea (Copepoda, Oncaeidae) in the North Pacific Ocean with focus on morphological variability. - Cho, K.H., C. Park & R. Böttger-Schnack (ZooKeys, 2021)
Three species of Spinoncaea Böttger-Schnack, 2003 are newly recorded in three locations of the equatorial and temperate Pacific Ocean collected by using a net of 60 μm mesh size. For all three species, morphological characters and patterns of ornamentation were analyzed in detail and illustrations of both sexes, also including form variants of the females, are provided. For the first time, information about the variability of various continuous (morphometric) characters are given, such as the spine lengths on the rami of the swimming legs or the proportions of urosomites. The complementary morphological descriptions of the Pacific specimens focus on similarities or modifications of characters as compared to earlier descriptions of these species from the type locality and various other localities. For S. ivlevi (Shmeleva, 1966), originally but insufficiently described from the Adriatic Sea, the Pacific material is similar in most aspects to the comprehensive redescription of the species from the Red Sea and from the type locality, except for a difference in the morphometry of the distal endopod segment on the antenna, which is discussed here. For S. tenuis Böttger-Schnack, 2003, and S. humesi Böttger-Schnack, 2003, the Pacific material mostly coincides with the characteristic features as described in the original account from the Red Sea. For all three species, differences and/or additions in ornamentation details were found in Pacific specimens (e.g., on the intercoxal sclerite of the first swimming leg or on the genital somite of the male) and females with aberrant morphology were detected. Genetic analyses based on 12S srRNA revealed for two species, S. ivlevi and S. humesi, little or no differences in genetic sequences between Pacific specimens and those recorded from the Mediterranean Sea, thus demonstrating that specimens from both locations are conspecific. For S. tenuis, for which no comparable genetic data are available, 12S srRNA amplification was unsuccessful as was the amplification of mitochondrial COI (barcoding) for all three species. The applicability of using COI amplification for barcoding of oncaeid copepods is discussed.